TIME STIRRING EFFECT OF CHITOSAN FROM SHRIMP SHELLS AS GOLD ABSORBENT - Prasetya, Dwi Sabda Budi; Ahzan, Sukainil (Lensa: Jurnal Kependidikan Fisika, 2019)
This study aims to analyze the effect of chitosan stirring time from shrimp shells as gold absorber. Experimental research was conducted in this study, where the manufacture of chitosan from shrimp shells began with demineralization (mineral removal) using 1.5 M HCl, deproteination (protein removal) using 3.5% NaOH and deacetylation (acetyl removal) using 60% HCl. The chitosan formed was weighed 0.1 gram (as many as five samples) and then stirred in a 10 ppm Au solution, with a stirring time of 0, 10, 20, 30, and 40 minutes, and its absorption ability to gold was analyzed using AAS (Atomic Absorbsion Spectroscopy) and obtained percentage of absorption respectively 24.79%, 50.89%, 45.64%, 40.52% and 37.87%. From the results of the study, it was found that there was an effect of chitosan stirring time from shrimp shells as gold absorber and the highest absorption at 10 minute stirring was 50.89%.